Perolehan Kembali Status Kewarganegaraan yang Hilang - Sandy Cahyono (Lentera Hukum, 2016)
A person's citizenship is a very important thing, In the relationship of the state and the individual shows how important a person's citizenship is, whether a person includes a citizen ora foreigner is of great consequence in this public life. Citizenship is the membership of a country in a simple way as the country is a particular association or organization. A person can lose citizenship or without citizenship (patricide). The type of study used in this study is a normative law study that is a process for establishing a rule of law. The conclusion of the study is that when a person reclaims citizenship that a person will be entitled to the right of citizenship as regulated of law in a Number 12 of 2006 on Citizenship of the Republic of Indonesia KEYWORDS: Citizenship, Citizen Rights, Apatride.